Government Expenditure in Maluku: Autoregressive Vector Analysis - Jacobus Cliff Diky Rijoly (JIET (Jurnal Ilmu Ekonomi Terapan), 2019)
In 1999 Indonesian government implementing the law of regional autonomy, direct impact to this implementation is every province has to manage the economic development of each province. It also happened in Maluku province, the increase of the APBD (Regional Income and expenditure Budget) supposed to be a instrument of the economic growth in Maluku. But, in fact Maluku still a 4th poorest province in Indonesia and have a highest unemployment rate in Indonesia, the effectiveness of the budget realization become the main problem, according to the BPS Maluku (National Bureau of statistic, Maluku Branch) most of the government budget is using as a routine expenditure (83.4%) and the rest of it (29.68%) is using as a capital expenditure, which is can’t push the economic growth acceleration. This study uses a VAR (Vector Autoregressive) Model, to determine effect of the government spending to economic growth in Maluku and make a forecasting models to give a policy recommendation to the Government of Maluku Province, the data that used in this study is a time series data from 1997-2016 sourced from BPS Maluku.The result shows that the government expenditure in Maluku Province are determined by various variable both exogenous (government policy: such as Oil and Non-oil revenue) and endogenous variable (GDP and Fixed Capital formation). the other result of estimation using Impulse Response Function and Variance Decomposition analysis show all the variables in the short run and in the long run positively impact the Government Expenditure in Maluku.